2019
DOI: 10.1002/mgg3.623
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants of CYP21A2 in Vietnamese patients with congenital adrenal hyperplasia

Abstract: Background Congenital adrenal hyperplasia (CAH) (OMIM #201910) is a complex disease most often caused by pathogenic variant of the CYP21A2 gene. We have designed an efficient multistep approach to diagnose and classify CAH cases due to CYP21A2 variant and to study the genotype‐phenotype relationship. Methods A large cohort of 212 Vietnamese patients from 204 families was recruited. We utilized Multiplex Ligation‐depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Using the MLPA technique, the prevalence of large deletions and large gene conversions in the present study was found in 29/112 (25.9%) patients with the SW phenotype. The results were in agreement with the work of Ben Charfeddine et al, 2012, who reported gene deletion/conversion in 11/50 Tunisian patients (22%) ( Kharrat et al, 2004 ; Ben Charfeddine et al, 2012 ; Chi et al, 2019 ; Umaña-Calderón et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Using the MLPA technique, the prevalence of large deletions and large gene conversions in the present study was found in 29/112 (25.9%) patients with the SW phenotype. The results were in agreement with the work of Ben Charfeddine et al, 2012, who reported gene deletion/conversion in 11/50 Tunisian patients (22%) ( Kharrat et al, 2004 ; Ben Charfeddine et al, 2012 ; Chi et al, 2019 ; Umaña-Calderón et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of CAH has increased nationally, with an estimated increase from 150 children at NHP in Hanoi in 2004 to 1235 cases (325 with genotyping completed) in 2018 [ 62 ], representing a 723% increase over 14 years. Vietnam’s national NBS program now includes CAH (together with congenital hypothyroidism, glucose-6-phosphate dehydrogenase deficiency, galactosemia, phenylketonuria and other inborn errors of metabolism) and has determined the incidence of CAH in Vietnam at 1:9008 live births [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Molecular diagnosis assists with genetic counselling, and is strengthening diagnostic capacity [ 64 ]. A recent publication from Vietnam on genetic analysis of 212 people living with CAH reported six novel variants [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies from the USA, UK, Cuba, Vietnam, China, Sweden have reported the I2G splice variant as the most common pseudogene-derived mutation in their study cohorts [25][26][27][28][29][30]. In a mixed population study, New Maria I. et al reported I2G and V281Lmutations to be the prominent mutations identi ed in the largest cohort of 1507 subjects [31].…”
Section: Discussionmentioning
confidence: 99%